Recent Publications (Quarterly Journal of Economics, 1939)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 53, Issue 2, February 1939, Pages 322–327, https://doi.org/10.1093/qje/53.2.322 Published: 01 February 1939